Passive Prosthetic Ankle Design Based on Indonesian Anthropometry - Wahyu Dwi Lestari (Journal of Mechanical Engineering Science and Technology (JMEST), 2022)
Foot prosthesis is a replacement for the foot to overcome activity limitations due to disease, birth defects, accidents or amputations. Many foot prosthetics have been developed in recent years to treat patients. However, prostheses on the market today have drawbacks, including their high price, lack of comfort, stiff ankles, and low durability. The main objective of this study is to develop an existing ankle-foot prosthesis design that approximates the resemblance of a human foot according to the anthropometry of Asians, especially Indonesians. This study contains the design of a prosthetic foot with a skin design model and a support core. The prosthetic core supports the use of a compliance mechanism (CM) model that functions to connect the limb organs that have been amputated. The design process is carried out using the Solidwork software. Ankle foot prostheses are designed to be able to withstand a load of 100 kg and can be used for patients with a height range of 150 cm to 180 cm. Based on the design results, it is found that the prosthesis mass is lower than the lowest mass of the user, so it feels light, ergonomic and flexible when used.